Tissue expression of PPAR-alpha isoforms in Scophthalmus maximus and transcriptional response of target genes in the heart after exposure to WY-14643 - Urbatzka, R. (2018)
Peroxisome proliferator-activated receptors (PPARs) are involved in the regulation of lipid and carbohydrate metabolism and can be activated either by natural ligands as fatty acids or by synthetic ligands including several environmental chemicals. In this study, two PPARα isoforms (α1 and α2) were analyzed in turbot (Scophthalmus maximus) for a different tissue distribution. PPARα1 was ubiquitously expressed, while the PPARα2 was predominantly expressed in the heart. Following this result, turbot juveniles were exposed by injection to a synthetic selective PPARα agonist, WY-14643, for 14 days. Suppression subtractive hybridization (SSH) was performed with pools of heart samples of control and exposed fish to get insights into PPARα-regulated genes in the heart of juvenile turbot. Four genes were positively identified in the forward-subtracted and 12 genes in the reverse-subtracted cDNA SSH library, corresponding to the down-regulated and up-regulated genes in response to the WY-14643 treatment, respectively. The confirmation of these results in individual samples of juvenile turbot exposed to WY-14643 revealed a statistically significant mRNA induction of two cardiac muscle proteins (myosin light chain 2 and tropomyosin 4), which were shown to be involved in heart contraction and heartbeat regulation in other teleost species. Herewith, we showed for the first time that PPARα2 is predominantly expressed in the heart and that a PPARα agonist can induce the mRNA expression of cardiac muscle proteins in teleosts.